Comparison of Effects of an Endotracheal Tube or Facemask on Breathing Pattern and Distribution of Ventilation in Anesthetized Horses - Moreno-Martinez, Fernando; Byrne, David; Raisis, Anthea; Waldmann, Andreas D.; Hosgood, Giselle; Mosing, Martina (Frontiers in Veterinary Science, 2022)
Equine respiratory physiology might be influenced by the presence of an endotracheal tube (ETT). This experimental, randomized cross-over study aimed to compare breathing pattern (BrP) and ventilation distribution in anesthetized horses spontaneously breathing room air via ETT or facemask (MASK). Six healthy adult horses were anesthetized with total intravenous anesthesia (TIVA; xylazine, ketamine, guaiphenesin), breathing spontaneously in right lateral recumbency, and randomly assigned to ETT or MASK for 30 min, followed by the other treatment for an additional 30 min. During a second anesthesia 1 month later, the treatment order was inversed. Electrical impedance tomography (EIT) using a thoracic electrode belt, spirometry, volumetric capnography, esophageal pressure difference (ΔPoes), venous admixture, and laryngoscopy data were recorded over 2 min every 15 min. Breaths were classified as normal or alternate (sigh or crown-like) according to the EIT impedance curve. A mixed linear model was used to test the effect of treatment on continuous outcomes. Cochran-Mantel-Haenszel analysis was used to test for associations between global BrP and treatment. Global BrP was associated with treatment (p = 0.012) with more alternate breaths during ETT. The center of ventilation right-to-left (CoVRL) showed more ventilation in the non-dependent lung during ETT (p = 0.025). The I:E ratio (p = 0.017) and ΔPoes (p < 0.001) were smaller, and peak expiratory flow (p = 0.009) and physiologic dead space (p = 0.034) were larger with ETT. The presence of an ETT alters BrP and shifts ventilation toward the non-dependent lung in spontaneously breathing horses anesthetized with TIVA.